1047 Regional Audit: Valid and Informed Consent for Lower Limb Arthroplasty in Orthopaedic Surgery: Are We Doing Enough?. (19th August 2022) - Sohail, Z; Mills, R; Adebayo, O; Mamarelis, G; Acquaah, F; Subhash, S; Liew, I
Abstract: Aim: To investigate regionally the validity of the patient consent process for lower limb arthroplasty, compared to set data standards, with a view to investigating whether the consent process could be improved, and if so, how? Method: Regional data from 8 hospital trusts (50 data sets collected from each hospital) across England was collected retrospectively from May 1st, 2021, (25 THR, 25 TKR), collated and collectively analysed against agreed, pre-determined set criterion. Data standards included ascertaining whether alternatives to surgery were offered and exploring the likely benefits and risks. Capacity to consent for procedure-specific surgery was measured as patients' ability to understand, weigh up, retain, and communicate their decisions regarding surgery. Hospitals regional data was collectively analysed. Results: Capacity was only successfully fulfilled and documented regionally in 11.6% of hip and 13.9% of knee replacement surgeries, despite Consent Form 1 having been filled out in 94.8% and 88.5% of cases respectively, which were procedure specific in only 74.0% and 72.1% of cases. Conclusions: Significant improvement can clearly be made to an area of already such high clinical negligence claims. We propose a novel solution involving the digitalisation of the consent process, including multimedia surgical videos to better inform patients and reliably assist in establishing the validity of a patient's consent. The implications of this are limited not only to Orthopaedic surgery but could have far-reaching consequences across all surgical (and indeed medical) specialties, where obtaining valid and informed consent for procedures remains integral to quality patient care.